One-leg standing balance and sports activity - Hahn, T.; Foldspang, A.; Vestergaard, E.; Ingemann-Hansen, T. (Scandinavian Journal of Medicine & Science in Sports, 1999)
The objective of the present cross-sectional study was to estimate one-leg standing balance in athletes and to investigate the relationship with type and amount of sports activity. The study comprised 339 active, competitive, non-pregnant athletes, aged 14-24 years from two sports clubs in the county of Aarhus, Denmark. The athletes answered a questionnaire about occupation and sports activity. One-leg standing balance was measured as the maximum time of one-legged balancing. The mean of the maximum time of one-legged balancing was 29 s (interquartile range 11.25-33.5 s). One-leg standing balance was positively associated with years of participation in basketball and was not associated with sex and age. We conclude that participation in basketball may induce significantly adaptive effects on standing balance. Scand J Med Sci Sports 1999 Feb;9(1):15-8